2018
DOI: 10.1016/j.yebeh.2018.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Implicit attentional bias for facial emotion in dissociative seizures: Additional evidence

Abstract: This study sought to extend knowledge about the previously reported preconscious attentional bias (AB) for facial emotion in patients with dissociative seizures (DS) by exploring whether the finding could be replicated, while controlling for concurrent anxiety, depression, and potentially relevant cognitive impairments. Patients diagnosed with DS (n=38) were compared with healthy controls (n=43) on a pictorial emotional Stroop test, in which backwardly masked emotional faces (angry, happy, neutral) were proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 55 publications
4
16
2
Order By: Relevance
“…The best supported behavioural finding is an implicit/preconscious attentional bias towards emotional facial expressions in people with FND-seiz,27–29 which is linked to adverse life events,27 hypothalamic-pituitary-adrenal (HPA-axis) dysfunction28 and symptom severity 29. These behavioural data link directly to elevated amygdalar activity observed during implicit facial expression processing,48–50 which together suggest enhanced affective salience of these stimuli.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The best supported behavioural finding is an implicit/preconscious attentional bias towards emotional facial expressions in people with FND-seiz,27–29 which is linked to adverse life events,27 hypothalamic-pituitary-adrenal (HPA-axis) dysfunction28 and symptom severity 29. These behavioural data link directly to elevated amygdalar activity observed during implicit facial expression processing,48–50 which together suggest enhanced affective salience of these stimuli.…”
Section: Discussionmentioning
confidence: 98%
“…The attentional bias for angry faces correlated positively with sexual abuse history and basal cortisol levels,27 28 whereas attentional bias for happy expressions was positively associated with seizure frequency in another study 29. Emotional facial expressions also disproportionately disrupted ongoing cognitive processing in people with FND-seiz, including working memory30 and task-switching performance 31…”
Section: Emotional Processing In Fnd: a Narrative Reviewmentioning
confidence: 94%
“…Current models of DS and FND in general consider difficulties with emotion processing a pivotal affective-cognitive deficit (Pick et al ., 2019; Williams et al ., 2018). In line with our results, previous studies have suggested that DS patients have problems with recognising emotional faces, while at the same time having an increased attentional bias towards them (Bakvis et al ., 2009; Pick et al ., 2016, 2019). While most previous studies exploring emotion processing in FND or DS patients used emotional faces as affective stimuli, their presentation and function differed.…”
Section: Discussionmentioning
confidence: 99%
“…(2018)] in emotion recognition and categorisation tasks. Other approaches used the implicit processing of emotional faces as a disruption mechanism for ongoing attentional processes, without an explicit emotion recognition task encompassed in their paradigms (Bakvis et al ., 2009; Gul and Ahmad, 2014; Pick et al ., 2018; Szaflarski et al ., 2018). Overall, those studies as well as our own approach mostly lack a non-affective paradigm controlling for the influence of the emotional content itself in comparison with the task-induced effects.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that both higher-level endogenous attention control and lower-level automatic attentional orienting are impaired in FND. Deficits in voluntary attentional disengagement from emotionally neutral stimuli (14) and the abnormal automatic (pre-conscious) allocation of attention to facial affect (15), specifically to threat-related facial affect (16), were found in FND patients. Moreover, avoidance learning of negative stimulus was shown to be impaired in FND (17).…”
Section: Introductionmentioning
confidence: 99%